Advances in Bone Graft Materials - Huh, Jung-Bo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint considers studies related to the bone graft materials used for bone regeneration in dental and medical areas, and particularly studies on new development and development directions, such as synthetic bone and heterologous bone. Bone regeneration is one of the most important challenges in medicine. Previously, patients' autologous bones were collected and transplanted for bone regeneration, but this had many limitations. Many researchers are currently developing a method that surpasses the bone regeneration ability of an autologous bone, via the use of artificial bone or heterologous bone. By developing and commercializing more functional, more efficient graft materials, both medical standards and patients' quality of life will be improved. This reprint reflects some of the related studies, but its greatest contribution to the field is its suggestions for future research and possible developments in this area.